THE RESONANCE OF TRADITION: UNVEILING THE ECHOES OF THE GREAT VOWEL SHIFT IN MODERN ENGLISH - Malikov, Ulug‘bek (Educational Research in Universal Sciences, 2023)
This article investigates the long-lasting effects of the Great Vowel Shift (GVS) on the phonological landscape of Modern English. The GVS, which lasted from the late 14th to the early 18th century, was a watershed point in the history of English pronunciation. While its effect on current English has been extensively explored in historical linguistics, it remains a complicated and changing subject of investigation. This study uses a multifaceted method that combines sociolinguistics, acoustic phonetics, and historical linguistic analysis to explore the legacy of the GVS in modern English. The study intends to detect persistent vowel changes, evaluate their geographic distribution, and investigate the sociolinguistic variables determining their persistence by looking at both standardized and regional dialects. The results have the potential to shed light on the persistence of GVS-induced phonetic modifications as well as their function in forming linguistic variety within the larger context of Modern English. The study adds important new information to the continuing conversation on the dynamic interaction between spoken language in the present and past linguistic occurrences. This examination of English’s historical echoes offers an essential perspective for comprehending the complex web of linguistic change across time as the language continues to change. The study combines corpus linguistics and acoustic analysis, tracing the trajectories of vowel sounds impacted by the GVS using historical texts, modern language corpora, and audio recordings. The study intends to evaluate the acoustic features of current vowels compared to their Middle English counterparts and quantify the magnitude of changes in vowels using sophisticated acoustic phonetics methods. Sociolinguistic issues are important in the research since language evolution is not a uniform process. The study investigates how regional dialects, socioeconomic demography, and education influence the variance and permanence of GVS-induced vowel changes in various populations. The research attempts to give a detailed knowledge of the numerous impacts on current vowel pronunciation by investigating these sociolinguistic elements. Furthermore, the study explores the larger implications of GVS residues for language instruction, dialectal preservation, and linguistic identity perception. The study’s conclusions are important not just for historical linguistics but also for language instructors and linguists attempting to understand the difficulties of Modern English pronunciation. In conclusion, this article provides a thorough examination of the echoes of the Great Vowel Shift in Modern English. The study offers insight on the long-term influence of this historical phonological change on the varied range of English spoken today by integrating historical linguistic analysis, acoustic phonetics, and sociolinguistics. We acquire a better understanding of the persistence of linguistic traditions and the dynamic interplay between historical events and the ever-changing character of language as a result of this research.